PERAN TOTAL QUALITY MANAGEMENT DALAM PENGUATAN TATA KELOLA DAN MUTU PEMBELAJARAN DI PENDIDIKAN ISLAM (Institut Ummul Quro Al-Islami Bogor, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving the quality of education in Islamic educational institutions. The research method used is a literature review (library research) by examining various relevant scientific sources, including journals, books, and research reports. The findings indicate that TQM is a strategic approach to achieving effective, efficient, and sustainable educational quality through the principles of customer focus, total involvement, and continuous improvement. The implementation of TQM has been proven to enhance teacher performance, institutional management, and student and parent satisfaction. However, its implementation still faces several challenges, such as limited understanding of quality concepts, resistance to change, limited human resources, and inadequate infrastructure. Therefore, the success of TQM implementation largely depends on strong leadership commitment, human resource capacity building, and the development of a sustainable quality culture within Islamic educational institutions